2016
DOI: 10.1095/biolreprod.116.138438
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Suppresses Abortion Relates to an Increase in the CD44bright NK Subset in Recurrent Pregnancy Loss Model Mice

Abstract: Recurrent pregnancy loss (RPL), which mostly is of unknown etiology (unexplained RPL, uRPL), is defined as three or more consecutive spontaneous abortions. Some women with uRPL display a higher fraction and cytotoxicity of natural killer (NK) cells in the periphery and endometrium. Therefore, some uRPL cases have been explained by autoimmune abnormalities. The efficacy of intravenous immunoglobulin (IVIg) for uRPL has been confirmed in several clinical trials; however, its mechanism remains unknown, mainly bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…As a result, using PerCp‐Cy5.5‐conjugated anti‐mouse CD45, PE‐conjugated anti‐mouse F4/80 and APC‐conjugated anti‐mouse CD206 antibodies, CD45 + F4/80 + CD206 − M1 and CD45 + F4/80 + CD206 + M2 macrophage subpopulations were identified both in the spleen and the uterus on gd6 (Figure 1A ). Next, we used a low‐dose LPS‐induced abortion model (0.5 μg per mouse) 21 , 22 to investigate the dynamic changes of M1 and M2 macrophages after LPS treatment for 1, 3, 6, 12 and 24 hours. The results showed an overall increasing tendency of M1 cells, a decreasing trend of M2 cells and an increase in M1/M2 ratio, and significant differences between LPS‐injected mice and the control group were observed at 6 hours and afterwards (Figure 1B,C , and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, using PerCp‐Cy5.5‐conjugated anti‐mouse CD45, PE‐conjugated anti‐mouse F4/80 and APC‐conjugated anti‐mouse CD206 antibodies, CD45 + F4/80 + CD206 − M1 and CD45 + F4/80 + CD206 + M2 macrophage subpopulations were identified both in the spleen and the uterus on gd6 (Figure 1A ). Next, we used a low‐dose LPS‐induced abortion model (0.5 μg per mouse) 21 , 22 to investigate the dynamic changes of M1 and M2 macrophages after LPS treatment for 1, 3, 6, 12 and 24 hours. The results showed an overall increasing tendency of M1 cells, a decreasing trend of M2 cells and an increase in M1/M2 ratio, and significant differences between LPS‐injected mice and the control group were observed at 6 hours and afterwards (Figure 1B,C , and Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the abortion mechanism caused by M1/M2 imbalance, rescue experiments utilizing in vivo LPS‐induced abortion model are needed. Since high as well as low doses of LPS can induce abortion in mice, 22 we set up to optimize the treatment conditions. Mice were ip injected with different doses of LPS (0.5, 1.2, 1.5, 2 or 4 μg in 100 μL PBS per mouse) on gd6.…”
Section: Resultsmentioning
confidence: 99%
“… 31 Similarly, a high dose of intact type- immunoglobulin in an early period reduced miscarriages through NK cells in a mouse model of miscarriage induced by lipopolysaccharide. 32 High-dose IVIG treatment starting at 4–5 weeks of gestation might effectively restore normal immune environment, while the treatment starting at 6 weeks of gestation would be too late to yield the efficacy to restore fecundity. Modification of immune function by a high dose of IVIG during early pregnancy might reduce the number of miscarriages in humans, but the mechanism is still unknown and further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified a novel subset of NK cells, CXCR4 + CD56 bright decidual NK cells, which are insufficiently expressed in RM patients and RM model mice; in addition, adoptive transfer of these cells to NK cell‐deficient mice improves pregnancy outcomes (Tao et al, 2021). Notably, several studies conducted with a mouse model of RM suggested that the modulation of NK cells in abortion‐prone mice is able to promote pregnancy outcomes (Li et al, 2017; Nagamatsu et al, 2018; Rezaei Kahmini et al, 2020; Tanaka et al, 2016). T cells are also critical modulators of immunity.…”
Section: Current Opinions On Rmmentioning
confidence: 99%